Microplastic Pollution Profile in the Black Sea Region - Erkan Kalipci; Huseyin Cuce; Fulya Aydin Temel; Mehmet Ali Dereli; Aysun Turkmen (Current Innovations in Chemical and Materials Sciences Vol. 9, 2024)
In recent years, plastic pollutants have been mixed into ecosystems with different size variations as megaplastic, macroplastic, mesoplastic and microplastic due to their use in a wide range of sectors. Based on scientific data, the goal of this study was to provide an overview of the structure of research on the presence and dispersal of microplastics (MP) mixed into the environment in the Black Sea region. A total of 100 peer-reviewed articles related to the topic were considered in the review article. The current state of microplastic pollution in Türkiye Black Sea coast environments which includes marine, lake, stream and freshwater ecosystems, as well as aquatic organisms, and sources and characteristics of microplastic pollution were reviewed narratively. As a result, these emerging microplastics affect the socio-cultural-economic aspects through negative impacts on endemic aquatic species, biodiversity, nature tourism, wetland habitats, aquaculture, food chain, and environment-public health. The Black Sea is at risk for microplastic pollution as a result of the discovery of relatively high concentrations of microplastics in its water and aquatic organisms. This has demonstrated the urgency of looking into the causes, movements, and impacts of microplastics on aquatic life in lakes, streams, and oceans. It is advised that awareness-raising campaigns be launched immediately in collaboration with local governments, pertinent public institutions and organizations, and non-governmental organizations. Regular microplastic monitoring studies should be conducted in Türkiye, not only in the Black Sea Region but in all provinces.